Higher Frequency of Reoperation With a New Bicruciate‐retaining Total Knee Arthroplasty. Issue 1 (January 2017) - Christensen, Jesse C.; Brothers, Justin; Stoddard, Gregory J.; Anderson, Mike B.; Pelt, Christopher E.; Gililland, Jeremy M.; Peters, Christopher L.
Abstract: Background: With as many as 25% of patients reporting residual knee symptoms after primary total knee arthroplasty (TKA), alternative implant designs and surgical techniques have been proposed to further reduce these symptoms. There is growing evidence that retention of the anterior cruciate ligament (ACL) results in more natural knee kinematics; thus, implants with more normal joint mechanics could provide improved physical function postoperatively and reduce the amount of residual symptoms. Advancements in the bicruciate‐retaining (BCR) TKA implant design have been made, and based on these, we wished to compare the BCR with a more traditional cruciate‐retaining (CR) implant. Questions/purposes: (1) Was there a difference in the risk of reoperation after primary TKA between BCR and CR implant designs? (2) Was there a difference in the radiographic findings of radiolucent lines (RLLs) between the implant designs? (3) Was there a difference in patient‐reported and clinical outcomes between the two implant designs? Methods: Between January 2013 and May 2014, two surgeons performed 475 primary TKAs. During this time, 78 (16%) of these were performed with BCR implants and 294 (62%) with CR implants; the remainder were performed with anterior‐stabilized or more constrained designs as a result of increased deformity and/or ligamentous deficiencies. During this period, the general indications for BCR TKA were arthritic knees with only slight to moderate deformity and sufficient ligamentous integrity of both the ACL and posterior cruciate ligament. The indications for CR TKA were similar other than these patients presented with a deficient ACL. A total of 66 (85%) of the BCR and 237 (81%) of the CR TKAs were available for followup at a minimum of 12 months or when reoperation occurred before 12 months (mean, 18 months; range, 2‐32 months). With the numbers available, there were no differences between the groups in terms of age and sex, but the patients undergoing CR TKA had a greater mean body mass index (33 ± 7 versus 31 ± 5 kg/m 2, p = 0.032). The frequency of early reoperation was compared between the groups as were radiographic evidence of RLL, patient‐reported outcomes, and knee range of motion (ROM). Results: Knees in the BCR group had a higher frequency of all‐cause revision (5% [three of 66] versus 1.3% [three of 237]; hazard ratio (HR), 7.44; 95% confidence interval [CI], 1.24‐44.80; p = 0.028). Knees in the BCR group had a higher frequency of irrigation and débridement with component retention (HR, 0.07; 95% CI, 0.02‐0.28; p < 0.001). No differences were found between groups for subsequent manipulation (HR, 0.34; 95% CI, 0.08‐1.42; p = 0.137). The proportion of RLLs was greater in the BCR group (HR, 2.93; 95% CI, 1.62‐5.32; p < 0.001) compared with the CR group. There were no differences between the groups in terms of the Physical Function Computerized Adaptive Test scores, Global10 scores or knee ROM outcomes. Conclusions: Preliminary short‐term findings suggest the BCR implant has inferior survivorship and concerning radiographic findings when compared with a conventional CR implant with respect to complications after primary TKA. These findings raise concerns about the new BCR design; however, further randomized trials are necessary to determine superiority between alternative implant designs. Level of Evidence: Level III, therapeutic study.